Comparison of the effectiveness of two different combinations of oral ketamine and midazolam premedication in autistic children - Kural Ciğerli, Oya; Tuğrul, Mehmet; Yakupoğlu, Sezer; Kınacı, Cem; Akpir, Kutay (ENT Updates, 2012)
Objective: Effective premedication is one of the key factors for anesthetic management of autistic children. We designed a study protocol to compare two different dose regimens of midazolam plus ketamine for premedication of autistic children. Methods: We performed a prospective randomized double-blind study in 142 autistic children, aged 1-17 years, undergoing brain SPECT imaging procedure. Group I received oral 0.5 mg/kg midazolam with 3 mg/kg ketamine and Group II received oral midazolam 0.25 mg/kg with ketamine 6 mg/kg. Onset of sedation and sedation score just before the induction of anesthesia were recorded. Anxiety of children was assessed by a four point scale at admittance, during separation from parents and at venipuncture. Post-anesthetic recovery was assessed using the modified Aldrete score. Postoperative vomiting and any other side effects were recorded when seen. Ten days after the procedure, parents were interviewed for changes in behaviors, sleep disturbances and feeding difficulties. Results: Acceptable sedation scores were obtained in both groups. Success rates for parental separation and intravenous cannulation were higher than 85% in both groups. There were no differences between two groups in terms of sedation onset time, intravenous cannulation anxiety score, parental separation anxiety score, side effects and changes in behaviors, sleep disturbances and feeding difficulties. The only significant difference between two groups is sedation scores before induction of anesthesia. Children in high ketamine group had deeper sedation state than those in the other group. Conclusion: Our results showed that both dose regimens provided successful premedication in autistic children.